2014
DOI: 10.1016/j.jtumed.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of freeze-dried Fragaria x ananassa powder on alloxan-induced diabetic complications in Wistar rats

Abstract: Objectives: Strawberries contain antioxidant phytochemicals, which have been shown to beneficial against inflammation, cardiovascular disease, cancer, obesity, neurodegeneration, hyperglycaemia and associated diabetic complications. Freeze-dried strawberry powder (FSP) is effective in controlling metabolic syndrome and cardiovascular risk factors. The present investigation was designed to evaluate the effect of FSP on alloxan-induced diabetes in rats.Methods: Diabetes was induced in male Wistar albino rats by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…Special attention is also paid to understanding the nature of postharvest changes in the chemical profile and physical properties of strawberry fruits in different storage conditions [3]. Despite the significance of strawberry as a food, pharmaceutical interest is also given due to the presence of various bioactive compounds including antioxidative [4], anti-inflammatory [5], antibacterial [6], anti-allergic [7], antidiabetic [8], and cancer preventive [9] properties. The antioxidative properties of various strawberries were discussed previously, and high effectiveness was revealed for Fragaria extracts and unprocessed fruits [10], thereby strengthening the interest to study strawberries.…”
Section: Introductionmentioning
confidence: 99%
“…Special attention is also paid to understanding the nature of postharvest changes in the chemical profile and physical properties of strawberry fruits in different storage conditions [3]. Despite the significance of strawberry as a food, pharmaceutical interest is also given due to the presence of various bioactive compounds including antioxidative [4], anti-inflammatory [5], antibacterial [6], anti-allergic [7], antidiabetic [8], and cancer preventive [9] properties. The antioxidative properties of various strawberries were discussed previously, and high effectiveness was revealed for Fragaria extracts and unprocessed fruits [10], thereby strengthening the interest to study strawberries.…”
Section: Introductionmentioning
confidence: 99%
“…The major phenolic compounds from strawberry-like quercetin, ellagic acid, and catechin, in their pure form, have been reported to have antidiabetic activities [ 49 , 50 , 51 ]. An extensive literature search indicated that there are very few previous reports on the effects of whole strawberry extracts or that of individual active molecules isolated from the extracts on diabetes [ 30 , 31 , 52 ]. To the best of the authors’ knowledge, the present report is the first comprehensive report investigating the effect of whole fruit extracts of strawberry on streptozotocin-induced diabetes at biochemical, molecular, and histological levels.…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanin extracts from strawberries caused upregulation of anti-inflammatory adiponectin gene in isolated rat adipocytes and in white adipose tissue in mice [ 29 ]. A recent report by Abdulazeez [ 30 , 31 ] has even suggested complete reversal of alloxan-induced diabetes and its complications after the administration of a powder from freeze-dried strawberries. None of the above reports have analyzed the effects of interventions at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…The commercially-available strawberry freeze-dried powder was demonstrated by Abdulazeez [88] to reverse alloxan-induced diabetes (results not presented in Table 4 as authors used commercial powder product); in a similar study, Yang et al [12] evaluated the potential anti-diabetic application of new and known compounds isolated from strawberry fruits (as presented in Section 2) by determining the α-glucosidase inhibitory activity. The best results were obtained for cupressoside A (IC 50 = 25.39 µM), kaempferol 3-(6-methylglucuronide) (IC 50 = 65.22 µM), and 2-p-hydroxybenzoyl-2,4,6-tri hydroxyphenylacetate (IC 50 = 97.81 µM), with very good results obtained for a newly proposed structure (kaempferol 3-(6-butylglucuronide)-IC 50 = 107.52 µM); results superior to the positive control (acarbose-IC 50 = 619.94 µM) were also obtained for five other compounds.…”
Section: Other Potential Applicationsmentioning
confidence: 99%